Memahami Asnaf Zakat di Era Sekarang (Analisis Qs. Al-Taubah [9]: 60 Melalui Pendekatan Qira’ah Muntijah Nashr Hamid Abu Zayd: A CRITICAL STUDY OF NĀṢR ḤĀMID ABŪ ZAYD’S QIRĀ’AH MUNTIJAH PERSPECTIVE - Anshori, Muhammad Helmi; Zakiy, Ahmad (Tanzil: Jurnal Studi Al-Quran, 2024)
This paper departs from Q.S. At-Taubah [9]: 60 which requires zakat for a Muslim to be distributed to the recipients of zakat as a way to purify themselves. If we understand the verse textually, there will certainly be no significant problems, because the target of the verse is indeed relevant to the needs of the Prophet’s society 14 centuries ago. However, what if one of the eight groups mentioned in the Qur’an is no longer found today? Departing from this anxiety, the author wants to reinterpret the concept of zakat and the recipients of zakat with the Qirā’ah Muntijah approach of Naṣr Ḥāmid Abū Zayd. This paper is a literature study, whose data source is through the verses of the Qur’an that specifically discuss the concept of zakat. Then the verses are analyzed using Qirā’ah Muntijah which is then described as the result of contextual interpretation of zakat. The result of this paper is that the eight groups of zakat recipients in Q.S. At-Taubah [9]: 60 is a mustaḥiq concept that is by the social context when the verse is revealed. At that time the groups of zakat recipients as mentioned in the verse, still existed. Furthermore, the purpose of the verse is to empower weak communities in terms of financial needs, which was the need of the community at that time. In the present context, the verse can be allocated to other groups such as: the insane, the blind, the homeless, people with disabilities, the Palestinian mujahids, the students, the teachers, the domestic assistants who are abused by their employers, the lowly laborers who are still shackled by their employers, and the refugees of other natural disasters.